Strategi Bisnis Dalam Perspektif Manajemen Sebuah Review Literatur (Jurnal Manajemen Kreatif dan Inovasi, 2023)
Business development in the world has entered the era of free competition not only in a small scope but a large scope, this creates fierce competition between companies. Efforts made by a company to win a market by providing advantages in competition, analyzing competing companies, and implementing effective marketing strategies. This study uses Literature Review research with the results of research that management strategies are oriented towards developing macro strategies such as product strategy development, pricing implementation strategies, acquisition strategies, market development strategies, financial and other strategies. The steps of strategy management include: internal and external environment scanning (Internal &; External Scanning), Strategy Formulation, Implementation, Function Control and Evaluation.